The Power Loss Optimization of a Current Fed ZVS Two-Inductor Boost Converter With a Resonant Transition Gate Drive - Li, Q.; Wolfs, Peter (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2006)
This paper develops a power loss optimization method in a current fed zero-voltage switching (ZVS) two-inductor boost converter, which is suitable for the module integrated converter applicationsin grid interactive photovoltaic systems. The paper conducts the numerical analysis of the variable power loss components and establishes a set of the circuit parameters for an optimized operatingpoint with a minimized average power loss. The ZVS twoinductor boost cell is fed from a sinusoidally modulated two-phase synchronous buck converter with an interphase transformer and produces a rectified sinusoidal voltage, which can be applied to an unfolding stage to generate the grid compatible voltage. The boost cell is also equipped with a resonant transition gate drive circuit to reduce the power loss in the drive circuit under high frequency operations. The experimental results for a prototype 1-MHz 100-W ZVS two-inductor boost converter are presented at the end of the paper.